Bad seed - Sala, Sharon (Naperville, Illinois : Sourcebooks Casablanca, 2025)
"It's love at first sight when head pastry chef Brendan Pope meets private investigator Harley Banks at the Serenity Inn in Jubilee, KY. Harley is staying there for her latest investigation. But unknown to them both, Harley has a hitman after her, courtesy of the wrong-doer she put behind bars on her last case. The FBI gets involved to clean up the loose ends so Harley can continue the investigation at the inn. But after nearly losing her, Brendan will stop at nothing to make sure Harley is safe and the criminals get their comeuppance"--
Keywords: Man-woman relationships -- Fiction; Bakers -- Fiction; Pastry -- Fiction; Women private investigators -- Fiction; Auditing -- Fiction; Murder for hire -- Fiction; Vendetta -- Fiction; Kentucky -- Fiction; Romance fiction; Thrillers (Fiction)